PENGARUH KECEMASAN PANDEMI COVID-19 TERHADAP KEPATUHAN IMUNISASI DASAR DI KABUPATEN ROKAN HILIR - Ade Noviani (Universitas Pahlawan Tuanku Tambusai, 2022)
During the COVID-19 pandemic, immunization services did not run optimally, during the COVID-19 pandemic resulted in a decrease in basic immunization coverage. In Rokan Hilir Regency, Riau Province, 3060 babies were not immunized in 2021 due to the pandemic. The purpose of this study was to determine the relationship between the influence of COVID-19 pandemic anxiety on basic immunization compliance in Rokan Hilir Regency. The type of research used is observational with an analytic cross-sectional study. The sample in this study were 371 respondents. Data analysis was performed by univariate, bivariate and multivariate. The results of the bivariate study of Covid-19 pandemic anxiety variables related to basic immunization compliance were knowledge (p value = 0.015), mother's attitude (p value = 0.033), family support (p value = 0.023), distance of service (p value = 0.040), mother's education (p value = 0.029), mother's occupation (p value = 0.030). Variables that have a causal relationship with pandemic anxiety, knowledge, mother's attitude, family support and distance. The conclusion in this study is that there is a relationship between pandemic anxiety with immunization compliance. It is recommended that every respondent who immunizes toddlers should be more obedient in bringing immunizations to toddlers so that the toddler's immune system increases so that toddlers are far from diseases that attack the immune system by getting clear information.